Contrasting metamorphic records and their implications for tectonic process in the central Sør Rondane Mountains, eastern Dronning Maud Land, East Antarctica - Tatsuro Adachi; Tomokazu Hokada; Yasuhito Osanai; Nobuhiko Nakano; Sotaro Baba; Tsuyoshi Toyoshima (2016)
Metamorphic rocks in the central part of Sør Rondane Mountains, eastern Dronning Maud Land, East Antarctica, are classified into three types based on petrological characteristics. (i) The Austkampane area preserves c. 800 °C and 0.5–0.6 GPa peak metamorphic conditions followed by decompression and subsequent isobaric cooling and later hydration (A-type). (ii) The Brattnipene and eastern Menipa area preserve peak P–T conditions of c. 800 °C and 0.7–0.8 GPa with subsequent isobaric cooling and later hydration (B-type). (iii) The area including Lunckeryggen, southern Walnumfjella and western Menipa preserves an amphibolite–facies peak metamorphic condition with signatures of prograde metamorphism (L-type), which are typically unaffected by the retrograde hydration event. Peak granulite–facies metamorphism of A- and B-type rocks are contemporaneous at c. 640–600 Ma, but a difference in the P–T paths between these rocks can be explained by thrusting of the A-type rock unit onto the B-type rock unit. By contrast, the timing of the metamorphism of the L-type rocks is significantly younger at c. 550 Ma, possibly related to the intrusion of pegmatites and granitoids. These metamorphic records in the central part of the Sør Rondane Mountains can be a test ground for the regional tectonic processes proposed for the orogeny related to Gondwana formation.